Building Capabilities of Youth Through Participatory Oral History Project: The South Hebron Hills, a Palestinian Case Study. Issue 1 (2nd January 2022) - Soliman, Mahmoud; Sulin, Laura; Karlıdağ-Dennis, Ecem
ABSTRACT: Drawing from the capabilities approach (Sen 1999 ; Nussbaum 2000 ) and reflecting on Fricker's (2007 ) epistemic (in)justice, this paper seeks to explain how a participatory oral history project enabled youth researchers in Palestine to increase their capabilities to participate in political and social life in their communities by fostering their attachment to the land and by increasing understanding of their cultural heritage. Due to the occupation, Palestinian youth researchers have been exposed to epistemic inequalities. They have been systematically prevented from exercising their political functionings; they cannot voice their ideas on freedom, heritage and land. Findings show that through participatory research, the youth researchers took an active role in their communities to cultivate their epistemic abilities to be the narrators of their own stories and to create public advocacy. Whilst acknowledging the intersectional power dynamics and oppression that govern their lives, the paper explores the possibility of participatory research in redressing epistemic injustices caused by structural inequalities and in disrupting colonial relations of domination. The research indicates that even in politically fragile contexts, participatory research can promote critical reflection, challenge the social imaginaries stigmatising the youth, and provide opportunities to develop political capabilities for social and public advocacy.